Makanan Tradisional Sentani dalam Perspektif Linguistik Kuliner - Siswanto Siswanto; Basori Basori; Wigati Yektiningtyas; Winci Firdaus (Ranah: Jurnal Kajian Bahasa, 2025)
This research aims to explore the ingredients and methods of food processing in the Sentani community. The Sentani community who live around Lake Sentani, Jayapura Regency, Papua have unique ingredients and methods, which are certainly different from other cultures. The qualitative method was chosen because this research intends to explain the complex concept of food and tradition in the Sentani culture. This research combines the perspectives of anthropological linguistics and culinary linguistics. The concept of anthropological linguistics will help in understanding the language and meaning of the terminology used in naming food and eating traditions. While culinary linguistics will help holistically understand the names of food in the context of the culture and beliefs of the Sentani community. The naming of ethnic Sentani food is divided into several categories, namely: new naming based on the absorption of other languages, naming based on the mention of the main ingredients, naming based on processing, naming based on the mention of similarity in shape, naming based on cooking tools/places, and naming based on customary methods/rules. The meaning of Sentani ethnic food based on the language used by the tribe is the Sentani regional language. The meaning of the naming of Sentani ethnic food is based on the ingredients used, taste, form of processing and presentation. Abstrak Riset ini bertujuan untuk mengeksplorasi bahan dan cara pengolahan makanan dalam masyarakat Sentani. Masyarakat Sentani yang hidup di sekitar Danau Sentani, Kabupaten Jayapura, Papua memiliki bahan dan cara yang khas, yang tentunya berbeda dengan kebudayaan yang lain. Metode kualitatif dipilih karena riset ini bermaksud menjelaskan konsep yang kompleks makanan dan tradisi dalam kebudayaan Sentani. Riset ini menggabungkan sudut pandang linguistik antropologi dan linguistik kuliner. Konsep linguistik antropologi akan membantu dalam memahami bahasa dan makna terminologi yang digunakan dalam penamaan makanan dan tradisi makan. Sedangkan linguistik kuliner akan membantu secara holistik memahami nama-nama makanan dalam konteks budaya dan keyakinan masyarakat Sentani. Penamaan makanan etnis Sentani terbagi atas beberapa kategori, yaitu: penamaan baru berdasarkan serapan bahasa lain, penamaan berdasarkan penyebutan bahan utama, penamaan berdasarkan pengolahan, penamaan berdasarkan penyebutan keserupaan bentuk, penamaan berdasarkan alat/tempat masak, dan penamaan berdasarkan cara/aturan adat. Makna makanan etnis Sentani berdasarkan bahasa yang digunakan suku tersebut adalah bahasa daerah Sentani. Makna penamaan makanan etnis Sentani didasarkan atas bahan yang digunakan, rasa, bentuk pengolahan dan penyajian.